VERBA GERAK IKU & KURU DAN PADANANNYA DALAM BAHASA INDONESIA - Ningsih, Ewida; Aibonotika, Arza; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: There are many types of motion verbs in Japanese and Indonesian, but this research focus on iku and kuru with its equivalent in Indonesian. In this research explains the meaning of motion verbs iku and kuru using the typology study with the aims to find out the similarities and differences in Japanese and Indonesian. In addition, it explains the core components of movement verbs such as „source‟, „goal‟, and „path‟ as well as case grammar in Japanese. The method used in this research is the translational equivalent method, which match the motion verbs iku and kuru equivalent in Indonesian. The results of this research, not all the words iku and kuru can be matched with the words 'pergi' and 'datang', because in Indonesian the words 'pergi' and 'datang‟ are deictic.Key Words : Motion verbs, case grammar, deictics, identifying method